Notes on the biology and fisheries of the blue swimming crabs, (Portunus pelagicus), in Leyte Gulf, Dulag, Leyte - Dioso, Kristine Joyce I. (2014)
A total of 155 crab samples with an average weight of 152.9 grams were caught by crab fishers in Dulag from Leyte Gulf, March to April 2014.Out of these 155 crabs, 92 were male species with a percentage distribution of 59% and the other 63 were female species with a percentage distribution of 41%. Of the 63 females, only 7 were berried. Weight, carapace length, and width were taken to the laboratory for assessment. The carapace length of all the samples obtained ranged from 5.0-9.0 cm where most measured from 6.0-6.4 cm in both male and female species. The carapace width however, ranged from 10.0-16.5 cm wherein most males were sized 14.0-14.4 cm and 13.0-13.4 for most of the female ones. It was observed that all of the crabs were sexually mature with males being heavier than females. Furthermore, 47 crab fishers were interviewed to determine the socio-economic profile and their fishing techniques and practices. Results showed that all of the crab fishers used motorized boats wherein some use both gill nets and crab pots. Not all of them were full-time crab fishers and boat owners though.